2020
DOI: 10.1108/ejmbe-08-2020-0244
|View full text |Cite
|
Sign up to set email alerts
|

Campaign participation, spreading electronic word of mouth, purchase: how to optimise corporate social responsibility, CSR, effectiveness via social media?

Abstract: PurposeThe purpose of this paper is to investigate how to optimise corporate social responsibility (CSR) when communicating via social media. In particular, the communication type, cause proximity and CSR motives are addressed facing the increased demand for transparency and the grown consumers' expectations towards socially responsible brands.Design/methodology/approachOnline survey was developed, based on a profound literature review and a field research we did on the actual social media behaviour of sociall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 45 publications
3
26
0
1
Order By: Relevance
“…Likewise, the consumers also want to support a socially responsible bank by increasing their purchase likelihood. These results of the present study are also supported by different researchers in the extant literature [10,43,50,113,114]. This survey has some important theoretical and practical implications.…”
Section: Discussionsupporting
confidence: 89%
“…Likewise, the consumers also want to support a socially responsible bank by increasing their purchase likelihood. These results of the present study are also supported by different researchers in the extant literature [10,43,50,113,114]. This survey has some important theoretical and practical implications.…”
Section: Discussionsupporting
confidence: 89%
“…So, the findings of the present study confirmed that customer CSR engagement on social media positively relates to E-WOM and purchase intentions. This study is not the first one to present these arguments because the arguments also receive support from contemporary researchers including Badenes-Rocha, Ruiz-Mafé, and Bigné [47]; Bialkova and Te Paske [58]; and Chu and Chen [64].…”
Section: Discussionmentioning
confidence: 89%
“…Positive WOM refers to a good communication about a company that the customer is willing to share with others [57]. When customers spread positive communication about an organization or brand thorough social media or internet, then it is regarded as E-WOM [58].…”
Section: Literature Review and Theoritical Supportmentioning
confidence: 99%
“…In particular, the sudden outbreak of the COVID-19 pandemic has furthered a digitalized transformation of human interaction where there is a reported increase in the users of social media (Lep et al, 2020 ; Vanko et al, 2021 ). Meanwhile, social media can be utilized by companies to extend businesses to a wider audience with a global reach and affect the behavioral intention of consumers while engaging in their CSR initiatives (Bialkova and Te Paske, 2020 ; Kuhzady et al, 2020 ). However, through a review of a study, the academy concerning CSR practices lags behind the practices of CSR engagement through social media (Kesavan et al, 2013 ; Chu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%